Conformation‐specific crosslinking of mitochondrial complex I. Issue 7 (27th February 2013) - Ciano, Margherita; Fuszard, Matthew; Heide, Heinrich; Botting, Catherine H.; Galkin, Alexander
Abstract : ND3 and NDUFA9 physically interact by cross‐linking study (View interaction) Abstract : ► Active and dormant forms of mitochondrial complex I were assessed by crosslinking. ► ND3 and 39 kDa subunits were specifically crosslinked only in the dormant form. ►No conformation‐specific crosslinking were found in the active form. ► In mitochondria complex I 39 kDa subunit is located close to ND3.